COMMUNITY BEHAVIOR TOWARDS ENVIRONMENTAL CLEANLINESS IN KAMPUNG AGAS AREA TANJUNG UMA VILLAGE BATAM CITY - Wulandari, Naomi; Widodo, Teguh; Resdati, Resdati (Jurnal Pendidikan Sosiologi dan Humaniora, 2023)
Cleanliness of the environment around the community is a very important and main thing to maintain. As humans who live close to nature, especially close to the sea, should always be able to care for, maintain, preserve, and participate in managing without polluting the environment, so as to create marine life and a clean environment and a healthy community. This study aims to find out how public awareness relates to waste problems in the environment and factors that affect public awareness in Agas Village. This study used descriptive quantitative methods. The population of this study was the community in Agas Village which amounted to 102 people with a sample of 73 respondents using Isaac and Michael's table on determining sample sizes with error rates of 1%, 5%, and 10%. Sampling using a simple random sampling technique (simple random sampling). Based on the results of the study, it can be concluded that public awareness of environmental cleanliness related to waste problems is categorized as very low public awareness with a percentage of 93.1%, this is seen by the number of pendent res who never and rarely do things related to environmentally conscious behavior. The factor that influences awareness the most influential are the knowledge factor with a percentage rate of 57.6%.